The prevalence and characteristics of chronic musculoskeletal pain in adult triathletes in South Africa - Francis, Glenda Chantelle (Department of Health and Rehabilitation Sciences, 2023)
Background Chronic pain, a growing problem globally, affects 11% to 55% of the world's adult population. The prevalence of chronic musculoskeletal pain amongst adult triathletes is unclear due to conflicting prevalence reports. The rise in sport participation at professional, amateur, and recreational levels, has led to an increase in the incidence of sports-related injuries among athletes and suggests that the prevalence of musculoskeletal injuries amongst triathletes, in particular, could also be increasing. However, pain and injury don't always go hand-in-hand. There is consistent support for exercise induced analgesia and pain perseverance in athletes. The lack of prevalence studies of chronic musculoskeletal pain in adult triathletes does not provide a definitive estimate of prevalence, and therefore leaves a gap in our understanding of chronic pain, and the characteristics thereof, in this population group. Therefore, two studies were conducted: (i) a systematic review of the literature to determine the prevalence of chronic musculoskeletal pain in adult athletes competing in the sports of swimming, cycling and running and adult triathletes and (ii) a cross-sectional survey of South African triathletes to determine the prevalence of chronic musculoskeletal pain in this group. Methods Phase 1 : Systematic review A systematic review was developed according to the Preferred Reporting Items of Systematic Reviews and Meta-Analysis Protocol (PRISMA-P) guidelines (Shamseer et al., 2015) and registered on PROSPERO [ID: CRD42020214094]. A customized search strategy containing relevant words and terms was used to search the following databases: MEDLINE/PubMed (via EBSCOhost), Cochrane Library, SCOPUS, SCIENCEDIRECT and AFRICA-WIDE INFORMATION (via EBSCOhost), Academic Search Premier, CINAHL, PsycArticles and PsycINFO. The risk of bias tool for prevalence studies was used to evaluate risk of bias in eligible studies. Studies were pooled for meta-analysis using the random effects model to determine a summary estimate of the prevalence of chronic musculoskeletal pain in triathletes across included studies. Statistical significance was set at a level of p < 0.05. Phase 2: Cross-sectional survey A cross-sectional study was conducted online via the social media platforms of Triathlon South Africa (TSA) and all other triathlon and multisport clubs in SA who gave approval. A password protected online survey using Microsoft Forms was created making use of a consent form, demographic questionnaire as well as the Brief Pain Inventory (BPI), Pain Catastrophising Scale (PCS) and the Tampa Scale for Kinesiophobia (TSK). The sampling frame consisted of adult South African triathletes over the age of 18 years and currently participating in triathlon in SA in either the Sprint, Olympic, Half Iron Man or Iron Man distances. Sample size was calculated based on the estimated number of registered triathletes with TSA and its affiliated clubs. With a confidence level of 95% and a sampling of error of 5%, a sample of 333 would make our findings generalisable to the sampling frame. Ethical approval to conduct this study was granted from University of Cape Town, Faculty of Health Sciences, Human Research Ethics Committee. Results Phase 1: Systematic review The initial literature search returned 590 records of which 588 remained after removal of duplicates. Initial screening of titles and abstracts identified 48 studies eligible for full-text review. Chronic musculoskeletal pain is experienced by athletes and triathletes with a pooled prevalence of48.96% and is consistent with global prevalence rates for chronic pain of between 11% and 55%. None of the literature reviewed reported on the effects of gender, culture, and level of income as possible contributing factors for chronic pain and none of the studies reported on whether the participants were disabled by their pain. Phase 2: Cross-sectional survey 297 triathletes responded to the survey, a sample size sufficient for 89.19% confidence. The prevalence of chronic pain was 29.29%. The association between the presence of chronic pain, sociodemographic characteristics, training and injury history were explored by comparing each variable in those with chronic musculoskeletal pain to those reporting without chronic musculoskeletal pain. Triathletes reporting chronic pain were significantly older than their counterparts. Apart from swimming, where those with pain were spending significantly longer training, the respondents showed no significant differences in training history or training characteristics. Respondents with chronic pain had sustained significantly fewer triathlon related injuries in the past 6 weeks than those without chronic pain. Conversely, respondents with chronic pain sustained more triathlon related injuries in the past 12 months . Respondents with chronic pain lost fewer training days due to injury in the last 6 months but lost more training days due to injury in the last 12 months. Conclusion The aim of this study was to determine the prevalence and characteristics of chronic musculoskeletal pain in adult triathletes in South Africa. The results of the systematic review and the cross-sectional survey offer substantial support for the hypothesis that chronic musculoskeletal pain is prevalent among adult triathletes. Notably, even with our small sample size, the results of the cross-sectional survey show a significant level of chronic pain without disability in this athletic population. We hope that future studies will explore the differences between chronic pain and high impact chronic pain (chronic pain with associated disability) and the effect thereof on participation on meaningful life roles in athletes. The role of physiotherapy in treating people with chronic pain is to minimise disability associated with pain, in both athlete and non-athlete populations.